2002
DOI: 10.1002/cne.10239
|View full text |Cite
|
Sign up to set email alerts
|

Intratelencephalic connections of the hippocampus in pigeons (Columba livia)

Abstract: Behavioral experiments using ablation of the hippocampus are increasingly being used to address the hypothesis that the avian hippocampus plays a role in memory, as in mammals. However, the morphological basis of the avian hippocampus has been poorly understood. In the present study, the afferent and efferent connections of the hippocampus in the pigeon telencephalon were defined by injections, at various rostrocaudal sites, of neuronal tracers mainly into the triangular part located between its V-shaped layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
155
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(181 citation statements)
references
References 53 publications
24
155
1
1
Order By: Relevance
“…However, we preferred the Atoji's model because in our previous studies (unpublished data), a group of labeled neurons appeared in the contralateral APHm-APHim following the injection of HRP into the unilateral APHm-APHim in chickens. Similar results were also obtained in pigeons (Casini et al, 1986;Atoji and wild, 2002) and finches (Szekely and Krebs, 1999). In mammals, the commissural projection of the HF originates from the CA4 area of Ammon's horn (Siegel and Landis, 1974;Demeter et al, 1985).…”
Section: Nature Of the Origin Of Direct Hippocampo-cerebellar Projectionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, we preferred the Atoji's model because in our previous studies (unpublished data), a group of labeled neurons appeared in the contralateral APHm-APHim following the injection of HRP into the unilateral APHm-APHim in chickens. Similar results were also obtained in pigeons (Casini et al, 1986;Atoji and wild, 2002) and finches (Szekely and Krebs, 1999). In mammals, the commissural projection of the HF originates from the CA4 area of Ammon's horn (Siegel and Landis, 1974;Demeter et al, 1985).…”
Section: Nature Of the Origin Of Direct Hippocampo-cerebellar Projectionsupporting
confidence: 79%
“…Based on the neuropeptide distribution and fiber connections, Erichsen et al, (1991) in chicken, Casini et al, (1986) in pigeon, Szekely and Krebs (1996) in finch, and Kahn et al, (2003) in pigeon suggested that the V-shaped layer (perhaps including the triangular area) correspond to the Ammon's horn of mammals, the dorsomedial region (DM) may be a homologue with the dentate gyrus of mammals, and the dorsolateral region (DL) may be likely candidate of the subiculum or enthorhinal cortex of mammals. However, based on fiber connections of the neurons in avian HF and their sensibilities to lesions formed by kainic acid injection into the lateral ventricle, Atoji and Wild (2002, 2004) suggested a subdividing model in contrast to the one described above. According to this model, the V-shaped layer of birds is similar to the dentate gyrus of mammals, and they may be homologous.…”
Section: Nature Of the Origin Of Direct Hippocampo-cerebellar Projectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PFC is intimately connected to the hippocampus, and prefrontal-hippocampal interactions seem to play a major role during association learning (17,31). In contrast, the NCL has no direct connections to the hippocampus or surrounding structures (26,32,33). It is likely that this major anatomical difference could lead to differences in how the cognitive integration areas of birds and mammals process information during associative learning, such as the time point when prospective representations emerge in the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Available hodological data on input from the hippocampal complex and output to the hypothalamus (Krayniak and Siegel, 1978b;Atoji et al, 2002), as well as neurochemical data (Reiner et al, 1984b, Reiner, 1994, suggest homology of the lateral septal nucleus of birds with the nucleus of the same name in mammals. A comparable cell group is present in all reptilian orders (Brauth, 1984;Reiner, 1987;Smeets, 1994).…”
Section: Intrapeduncular Nucleus (Inp) 3 Intrapeduncular Nucleus (Inp)mentioning
confidence: 99%